2012
DOI: 10.1007/s10616-012-9453-2
|View full text |Cite
|
Sign up to set email alerts
|

The in vitro study of apoptosis in NB4 cell induced by citral

Abstract: Citral, 3,7-dimethyl-2,6-octadienal, is a key component of the essential oils extracted from several lemon-scented herbal plants. Besides its antifungal activity, the anticancer effect of citral was studied in recent years. In this study, we investigated the effect of citral on the acute promyelocytic leukemia cell line NB4. Citral treatment had an antiproliferative effect in NB4 cells via the induction of apoptosis assessed by morphology, proliferation assay, DNA electrophoresis, Annexin V-FITC/PI staining an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 16 publications
2
21
0
1
Order By: Relevance
“…A major hurdle in the use of citral as an anti-cancer therapeutic is the lack of understanding of the mechanism by which this monoterpenoid induces cancer cell death. While previous reports have demonstrated an increase in cleaved caspase-3 in cancer cells treated with citral34, the upstream mechanisms that result in the activation of this apoptosis-mediating caspase in these experiments are unclear.…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…A major hurdle in the use of citral as an anti-cancer therapeutic is the lack of understanding of the mechanism by which this monoterpenoid induces cancer cell death. While previous reports have demonstrated an increase in cleaved caspase-3 in cancer cells treated with citral34, the upstream mechanisms that result in the activation of this apoptosis-mediating caspase in these experiments are unclear.…”
mentioning
confidence: 73%
“…In vitro studies have reported on the ability of citral to induce cell death of breast cancer as well as leukemia cells34. In a model for chemically-induced skin cancer, chronic application of citral resulted in a decrease in the number of animals developing tumors5.…”
mentioning
confidence: 99%
“…In fact, suppression of NF-jB activity has become an interesting approach to render cancer cells more susceptible to chemotherapy (Karin et al, 2002). A recent study in leukemic NB4 cells illustrated that an inhibition of NF-jB protein involved in apoptotic effects of citral on these cells (Xia et al, 2013). It may be possible that citral may exert potentiating activity by this manner but this hypothesis needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it inhibited human breast cancer cell MCF-7 growth and induced cycle arrest in G2/M phase (Chaouki et al, 2009). Recently, Xia et al (2013) found that citral has apoptotic activity on acute promyelocytic leukemia cell lines (NB4 cells) and this effect was attributed to the activation of caspase-3 and down-regulation of nuclear factor kappa B (NF-jB) expression. Similarly, previous work from our laboratory have found that citral induced human lymphoma Ramos cell apoptosis by activating caspase activity in a concentration and time-dependent manner but has no effect on cell distribution in the cell cycle (unpublished observation).…”
Section: Introductionmentioning
confidence: 99%
“…Por tanto, la capacidad de los terpenos para inducir la muerte celular programada, es de gran interĂ©s oncolĂłgico (8)(9)(10).…”
Section: IntroduccciĂłnunclassified